ANALISA PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN (STUDI KASUS DI PT. X) - Francisca Hermawan; Yuvenny Christine (Center for Economic Studies Universitas Katolik Parahyangan, 2014)
One benchmark is a good resource to have good performance and one of the factors that a good performance is the provision of compensation to the employee. This study was conducted to determine whether there is a significant impact on the provision of compensation to the performance of the employee PT